Evolution of Regional Disparities in Romania - A Shift-share Analysis - Mihaela-Nona Chilian (European Regional Science Association (ERSA), 2011)
The paper aims to assess the evolution of the development disparities (output, employment, overall and by sectors) in the regions and counties of Romania. Using classic and spatial shift-share analysis tools, we investigate the extent to which the existing interregional and, especially, intra-regional and inter-county inequalities can be attributed to different factors, such as industry mix, regional specific factors, and interregional interactions. The results reveal a diverse milieu and offer useful insights both for general and specifically targeted policies in the area of regional development.
Keywords: O18; R11; R12; R15; 330; Romanian regions; regional disparities; shift-share analysis; regional development